Validitas dan Reliabilitas Instrumen Penilaian Pembelajaran Pendidikan Jasmani Olahraga dan kesehatan Materi Atletik Siswa Kelas VII SMP Sederajat - Sandy Heppy Kirana; Dona Sandy Yudasmara; Surya Adi Saputra (Jayabama: Jurnal Peminat Olahraga, 2024)
This research aims to develop a valid and reliable learning evaluation instrument. This research uses the development of this learning evaluation instrument using a development model based on Lee &; Owens theory, namely ADDIE, where this development model consists of 5 stages , namely Analysis , Design , Development, Implementation, Evaluation. Data collection in this study used a small scale of 40 samples and a large scale of 80 samples. Data analysis techniques by determining validity and reliability using IBM SPSS. From the results of the validity test carried out on the scale, namely the value of Rcalculate > Rtabel where if the results of Rcalculate > Rtabel then it can be declared that the instrument is valid. Meanwhile, in the validity test on a large scale, the results obtained are the value of Rcalculate > Rtabel where if the results of Rcalculate > Rtabel then it can be stated that the instrument is valid. In addition to validity tests, researchers also use reliability tests on small and large scales. In the results of small-scale reliability tests, the results obtained are Cronbach's Alpha value > 0.60, which means that the instrument has a high reliability value. And in large-scale reliability tests, the results obtained are Cronbach's Alpha value > 0.60, which means that the instrument has a high reliability value. The PJOK assessment instrument for athletic material for grade VII SMP/MTs students has proven to be valid and reliable. There is a need for further studies related to instrument development, where the instrument is still at the development stage where the data obtained is only validity and reliability data on a small and large scale, the instrument still needs to be evaluated so that the shortcomings that still exist can be corrected and addressed